Analisis Manajemen Pengembangan Pemasaran Online di Media Sosial Tiktok Lewat Data SWOT Travel Umrah PT Rihlah Saidah Haramain - Suadaa Irfana, Maisyatus; Chandra Maulana, Hero; Raihan, Alfandy; Kanaya Tabita, Egidia; Bagus, Satriyo (Journal of Comprehensive Science, 2025)
The number of Umrah travel throughout Indonesia makes competition between fellow travel companies, especially in the field of digital marketing, they must still be able to strive and continue to innovate in the digital content of Umrah travel companies. To make a comparison where a content is worthy of being aired on social media and can attract interest in consumers, but this has not been implemented perfectly. This study aims to examine the comparison of TikTok engagement rates of Rihlah Saidah Haramain and An Namiroh profiles to conduct a SWOT analysis to obtain innovations in the development of TikTok social media content Rihlah Saidah Haramain as an effort to conduct research on digital promotional content on the TikTok platform and create value with an online promotional digital marketing innovation. Using qualitative research methods with qualitative descriptive analysis techniques, the phenomenological research paradigm in the media is also used to interpret TikTok engagement rate data as a tool for innovation and creativity in the development of online promotions through TikTok with the final results of elaboration through SWOT.